Celecoxib and Afatinib synergistic enhance radiotherapy sensitivity on human non-small cell lung cancer A549 cells. (1st February 2021) - Zhang, Pan; Song, Erqun; Jiang, Mingdong; Song, Yang
Abstract: Purpose: Radioresistance is highly correlated with radiotherapy failure in clinical cancer treatment. In the current study, we sought to examine the efficacy of Celecoxib and Afatinib co-treatment as radiosensitizers in the management of non-small cell lung cancer (NSCLC) A549 cells. Materials and methods: Generally, A549 cells were cultured with the treatment of Celecoxib and/or Afatinib for 24 h. Then, the cells were exposed to irradiation at 2 Gy/min for 1 min. After the end of treatment, cell viability, clonogenic survival, apoptosis and Prostaglandin E2 (PGE2) Elisa assays were performed. Transcriptional levels of Cyclooxygenase-2 (COX-2) affected by Celecoxib and/or Afatinib were measured by RT-qPCR. Posttranscriptional level of epidermal growth factor receptor (EGFR)-related gene was measured by Western blotting analysis. Results: Here, we, for the first time, reported that the co-treatment of Celecoxib and Afatinib regulates the resistance of NSCLC A549 cells to radiation. The co-treatment of Celecoxib and Afatinib sensitized radiotherapy through the radiation-induced loss of cell viability and colony formation, as well as apoptosis. Mechanistically, Celecoxib and Afatinib-treated cells showed the inhibition of COX-2 and EGFR expression, which may be responsible for the A549 cells' increased resistance to radiation. Conclusion: Our results suggested that Celecoxib and Afatinib regulate cell sensitivity to apoptosis, and thus modulate the resistance of NSCLC to radiation.